The Impact of a Stabilization Exercise on Neck Pain: A Systematic Review and Meta-analysis - Wu, Binbin; Yuan, Hongyan; Geng, Deyu; Zhang, Liang; Zhang, Cheng (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Introduction The efficacy of a stabilization exercise for the relief of neck pain remains controversial. We conducted a systematic review and meta-analysis to explore the effectiveness of a stabilization exercise on neck pain.Methods We searched Embase, Web of Science, EBSCO Information Services, and the Cochrane Library databases through May 2019 for randomized controlled trials (RCTs) assessing the impact of a stabilization exercise on neck pain. This meta-analysis was performed using the random effects model.Results Six RCTs are included in the meta-analysis. Compared with the control group of patients with neck pain, a stabilization exercise can significantly reduce pain scores at 4 to 6 weeks (mean difference [MD]: −2.41; 95% confidence interval [CI], −4.46 to −0.35; p = 0.02), Neck Disability Index [NDI] at 10 to 12 weeks (MD:− 6.75; 95% CI, −11.71 to −1.79; p = 0.008), and depression scale at 4 to 6 weeks (MD: −4.65; 95% CI, −7.00 to −2.31; p = 0.02), but it has no obvious impact on pain scores at 10 to 12 weeks (MD: −1.07; 95% CI, −3.42 to 1.28; p = 0.37) or at 6 months (MD: −1.02; 95% CI, −3.43 to 1.39; p = 0.41).Conclusions A stabilization exercise can provide some benefits to control neck pain.
Keywords: stabilization exercise; neck pain; randomized controlled trials